Long-term NOx trends over large cities in the United States during the great recession: Comparison of satellite retrievals, ground observations, and emission inventories. (April 2015) - Tong, Daniel Q.; Lamsal, Lok; Pan, Li; Ding, Charles; Kim, Hyuncheol; Lee, Pius; Chai, Tianfeng; Pickering, Kenneth E.; Stajner, Ivanka
Abstract: National emission inventories (NEIs) take years to assemble, but they can become outdated quickly, especially for time-sensitive applications such as air quality forecasting. This study compares multi-year NOx trends derived from satellite and ground observations and uses these data to evaluate the updates of NOx emission data by the US National Air Quality Forecast Capability (NAQFC) for next-day ozone prediction during the 2008 Global Economic Recession. Over the eight large US cities examined here, both the Ozone Monitoring Instrument (OMI) and the Air Quality System (AQS) detect substantial downward trends from 2005 to 2012, with a seven-year total of −35% according to OMI and −38% according to AQS. The NOx emission projection adopted by NAQFC tends to be in the right direction, but at a slower reduction rate (−25% from 2005 to 2012), due likely to the unaccounted effects of the 2008 economic recession. Both OMI and AQS datasets display distinct emission reduction rates before, during, and after the 2008 global recession in some cities, but the detailed changing rates are not consistent across the OMI and AQS data. Our findings demonstrate the feasibility of using space and ground observations to evaluate major updates of emission inventories objectively. The combination of satellite, ground observations, and in-situ measurements (such as emission monitoring in power plants) is likely to provide more reliable estimates of NOx emission and its trend, which is an issue of increasing importance as many urban areas in the US are transitioning to NOx -sensitive chemical regimes by continuous emission reductions. Highlights: Derived multi-year urban NOx trend from satellite (OMI) and ground observations (AQS). Revealed NOx responses to the 2008 Economic Recession by OMI and AQS. The trend not well captured by emissions used for national air quality forecasting. Demonstrated how to use space and ground observations to evaluate emission updates.